Impact of the Covid-19 Pandemic on Distribution of Village Funds in 2021 - Ana Sopanah; Ndaru Muchtarom Anantadi; Dwi Anggarani; Khojanah Hasan (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2022)
This research aims to find out more about the process of channeling village funds and during the Covid-19 pandemic. This type of research uses a quantitative approach. The sample taken is a village located in the local government area which is a partner of the Bekasi KPPN as the manager of the distribution of Physical DAK and Village Funds. There are 738 villages in the Bekasi Regency area. The results of the study show that the Covid-19 pandemic has had an impact on the management of village funds, especially the distribution of village funds. These changes are outlined in several central government policies ranging from government regulations in lieu of laws to their derivatives. Realization of distribution of village funds between before and during the Covid-19 pandemic, the results found that the percentage between the ceiling and the realization of distribution of village funds before and during the Covid-19 pandemic was only 0.0001%. The government, through channeling village funds, is here to assist the process of national economic recovery.